Expanding the positive utility of travel through weeklong tracking: Within-person and multi-environment variability of ideal travel time. (April 2020) - Le, Huyen T.K.; Buehler, Ralph; Fan, Yingling; Hankey, Steve
Abstract: Travel has been found to have a positive utility—often measured as a desire for non-zero travel time. Although past studies have found that desired travel time varies by trip attributes, they often focused on a single trip purpose (e.g., commute) or single time point (e.g., peak period of one day) and rarely captured variation within individuals and across multiple travel environments. To address these limitations, we employed a smartphone-based travel behavior survey of 186 users making 4397 trips in the Washington, DC, and Blacksburg, VA metropolitan areas. For each user, multiple trips were recorded and the user was asked to repeatedly report on the ideal travel time for each trip. We found that desired travel time varied across different trip environmental characteristics and purposes. Ideal travel time was longer for active travel trips, leisure trips, weekend trips, and when the user conducted activities during trips (e.g., talking, using the phone, looking at the landscape) and traveled with companions. Our study suggests the need for more realistic estimation of the value of travel time savings and the need for quantifying the effect of multitasking during travel on people's willingness to reduce travel time. Practitioners should also consider providing better urban infrastructure for pedestrians and bicyclists to fulfill their trips, as their ideal travel times closely match actual travel times. Highlights: This study quantifies the effects of various trip attributes on ideal travel time. We employed a smartphone survey to repeatedly measure trips over 1–2 weeks per person. Ideal travel time was longer for leisure trips and trips by foot and bicycle. Talking and sightseeing during trips are associated with longer ideal travel time.